2005
DOI: 10.1111/j.1468-1331.2005.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Extra temporal involvement in herpes simplex encephalitis

Abstract: Temporal lobe abnormalities on brain imaging have been described as strong evidence for herpes simplex encephalitis (HSE) in appropriate clinical settings. Extra temporal abnormalities are less well described in these patients. We retrospectively reviewed 20 patients of HSE and found extra temporal involvement in 11 (55%) patients. Three patients (15 %) had pure extra temporal abnormalities. Twelve patients (60%) had temporal lobe involvement, four patients (20%) had pure temporal lobe involvement and five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 21 publications
4
40
1
3
Order By: Relevance
“…In the study conducted by Panisset et al, unilateral thalamic involvement was observed in 50% of the cases (18). Our results confirmed that the range of neuroradiological features varies in children as it has been described in previous studies and the proportion of extratemporal lesions is higher than it is in adults (3,12,19).…”
Section: Wwwjtomcorgsupporting
confidence: 81%
“…In the study conducted by Panisset et al, unilateral thalamic involvement was observed in 50% of the cases (18). Our results confirmed that the range of neuroradiological features varies in children as it has been described in previous studies and the proportion of extratemporal lesions is higher than it is in adults (3,12,19).…”
Section: Wwwjtomcorgsupporting
confidence: 81%
“…The authors concluded that ictal piloerection is predominately seen in patients with temporal lobe seizure foci and does not appear to correlate with laterality [1]. This finding dovetails with the characteristic pattern of temporal and insular lobe edema seen on MRI in patients with HSV encephalitis [2]. The associated focal piloerection seen in our patient is likely attributable to neuronal hyperexcitation of his left or right mesial temporal lobe given the MRI findings.…”
supporting
confidence: 62%
“…HSV has the ability to enter the central nervous system (CNS), and replicate in neurons and glia cells. The inflammatory process of HSE is characterized by hemorrhagic-necrotizing features and localized in the predilection sites within the fronto-temporal brain regions, albeit extratemporal manifestations can be observed on occasion [60,101].…”
Section: Pathogenesis Of Hsementioning
confidence: 99%